Psychological Safety and Employee Work Productivity: A Literature Review of Psychology and Human Resources - Raihan Saputra; Jumawan Jumawan; Yuarini Wahyu Pertiwi (Inovan Publisher, 2025)
Employee work productivity is a key factor influencing organizational effectiveness and competitiveness. In addition to technical and managerial factors, psychological factors have increasingly been recognized as important determinants of employee performance. One of these factors is psychological safety, defined as an individual's perception of being able to express opinions, ask questions, share ideas, and admit mistakes without fear of negative consequences. This study aims to review and synthesize previous research findings regarding the relationship between psychological safety and employee work productivity. This study employed a literature review method by analyzing relevant articles obtained from several academic databases, including Google Scholar, Scopus, ScienceDirect, SpringerLink, Wiley Online Library, and Taylor & Francis Online. The selected literature was reviewed systematically based on predetermined inclusion and exclusion criteria. The findings indicate that psychological safety has a positive relationship with employee work productivity. Employees who experience higher levels of psychological safety tend to engage in open communication, knowledge sharing, collaboration, and innovative behavior, which contribute to improved work effectiveness and efficiency. Furthermore, psychological safety enhances work engagement and organizational learning, leading to better performance outcomes. In contrast, low psychological safety may hinder communication, increase work stress, and reduce productivity. The review highlights the importance of creating a psychologically safe work environment as a strategy for improving employee productivity and supporting sustainable organizational performance.